Life Insurance Risk Management Essentials - Koller, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The aim of the book is to provide an overview of risk management in life insurance companies. The focus is twofold: (1) to provide a broad view of the different topics needed for risk management and (2) to provide the necessary tools and techniques to concretely apply them in practice. Much emphasis has been put into the presentation of the book so that it presents the theory in a simple but sound manner. The first chapters deal with valuation concepts which are defined and analysed, the emphasis is on understanding the risks in corresponding assets and liabilities such as bonds, shares and also insurance liabilities. In the following chapters risk appetite and key insurance processes and their risks are presented and analysed. This more general treatment is followed by chapters describing asset risks, insurance risks and operational risks - the application of models and reporting of the corresponding risks is central. Next, the risks of insurance companies and of special insurance products are looked at. The aim is to show the intrinsic risks in some particular products and the way they can be analysed. The book finishes with emerging risks and risk management from a regulatory point of view, the standard model of Solvency II and the Swiss Solvency Test are analysed and explained. The book has several mathematical appendices which deal with the basic mathematical tools, e.g. probability theory, stochastic processes, Markov chains and a tochastic life insurance model based on Markov chains. Moreover, the appendices look at the mathematical formulation of abstract valuation concepts such as replicating portfolios, state space deflators, arbitrage free pricing and the valuation of unit linked products with guarantees. The various concepts in the book are supported by tables and figures.
What is Risk Management -- The role of the Balance Sheets and of Capital -- Accounting Principles -- Risk Appetite and Tolerance -- Key Insurance Processes and their Risks -- Financial Risks and their Modelling -- Insurance Risks -- Operational Risks -- Capital Models and Integrated Risk Management -- Risk adjusted performance Metrics -- Risk Management in a Group and Intra-group Transactions -- Products and their Risks -- Emerging Risks -- Regulatory view on Risk Management: Solvency II -- Governance and Organisation -- A Stochastic Processes -- B Application of the Markov model to Life Insurance -- C Abstract Valuation -- D An Introduction to Arbitrage Free Pricing -- E An Introduction to Stochastic Integration -- F CERA Comparison.
Keywords: Economics; Mathematics; Distribution (Probability theory).; Economics -- Statistics; Economics, Mathematical; Finance; Economics/Management Science; Game Theory/Mathematical Methods; Financial Economics; Insurance; Applications of Mathematics; Probability Theory and Stochastic Processes; Statistics for Business/Economics/Mathematical Finance/Insurance.